The effect of curing modes and times of third-generation Led LCU on the mechanical properties of nanocomposites = Efecto del modo y tiempo de fotocurado de la lámpara LCU Led de tercera generación en las propiedades mecánicas de los nanocompuestos - Oglakci, Burcu
This study evaluates the effect of curing modes and times on the mechanical properties of nanocomposites. Two nanocomposite resins were investigated: supra-nanohybrid (Estelite Posterior Quick; EP) and nanohybrid (Solare X; SX). They were polymerized with a light-emitting diode light-curing units (LED LCU, Valo) as follows: standard mode for 20s (ST20), high power mode for 12s (HP12), high power mode for 20s (HP20), extra power mode for 6s (XP6), and extra power mode for 20s (XP20). For Vickers microhardness (HV), disc-shaped specimens were fabricated (n=10). For the three-point bending test, bar-shaped specimens were fabricated (n=10). Flexural strength and resilience modulus were calculated. The fractured surfaces and specimen surfaces of composites were observed using scanning electron microscopy. The data were analyzed with repeated measures ANOVA, two-way variance, and Bonferroni tests (p<0.05). On the top and bottom surfaces of the EP nanocomposite resin, ST20 and HP12 revealed statistically higher HV than with XP6. Moreover, HP20 and XP20 had statistically higher HV than HP12 and XP6. For the SX nanocomposite resin, HP20 had statistically higher HV than HP12. For EP and SX, there were no significant differences in flexural strength and resilience modulus regarding the curing modes and times. Furthermore, SX demonstrated lower mechanical properties than EP. Scanning electron microscopy indicated that both nanocomposites had similar surface appearances. However, with all curing modes and times, SX exhibited layered fractures and more crack formations than EP. Different curing modes and times could influence the microhardness of nanocomposites.